Reduction of fibre bundle G(G/H, H) over submanifolds of space G/H. III - Vosilius, R. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Восилюс. Редукции расслоения G(G/H,H) над подмногообразием пространства G/H. IIIR. Vosilius. Išsluoksniavimo G(G/H, H) redukcijos virš erdvės G/H podaugdarių. III